Treatment of Chronic Pain Conditions : A Comprehensive Handbook - Pope, Jason E.; Deer, Timothy R. (Springer New York : Imprint: Springer, 2017)
There is an unmet need in both acute and chronic care settings for a comprehensive, clinically focused, fast reference on pain management. Written by high-profile, internationally recognized experts in field, Pain Treatment for Acute and Chronic Conditions: A Comprehensive Handbook is one of the first manuals of its kind to provide balanced and comprehensive coverage of pain medicine modalities. The book is structured into sixteen sections with each chapter providing key points for quick reference, followed by a more detailed overview of the topic at hand with extensive tables and figures to illustrate. Beautifully laid out and extensively furnished with both research and experience, this book is a necessary resource in the field of pain medicine.- Resumé vydavatel